A Systematic Review on Determinants of Financial Reporting Readability(Case Study: Iran's Securities and Exchange) - Nasrin Varmaziyar; Mahnaz Molanazari (پژوهش‌های تجربی حسابداری, 2025)
The current research is applied in terms of its objective, and it operates within the interpretive paradigm. The research sample consists of 31 articles published in business, management, and accounting journals indexed in the SID and ISC databases, covering the period from 2017 to 2022. The PRISMA checklist was employed to develop the review protocol, and the Critical Appraisal Skills Programme (CASP) rubric was used to assess the quality of the studies in the sample. The findings revealed that factors such as corporate governance, management characteristics, earnings management, audit characteristics, and corporate governance mechanisms are key determinants of reporting readability in Iran. Despite the limitations of the "Fog Index," this measure can still be effectively utilized in Iran’s stock market. Furthermore, it is significant to propose an Iranian model of factors influencing financial reporting readability, incorporating the key determinants identified in this study. The originality of this research lies in establishing a link between the findings and theoretical frameworks, an aspect often absent or insufficiently addressed in existing studies